Making organoruthenium complexes of 8-hydroxyquinolines more hydrophilic: impact of a novel l-phenylalanine-derived arene ligand on the biological activity. Issue 7 (23rd January 2018) - Movassaghi, Sanam; Hanif, Muhammad; Holtkamp, Hannah U.; Söhnel, Tilo; Jamieson, Stephen M. F.; Hartinger, Christian G.
Abstract : Introduction of anl -phenylalanine-derived arene ligand leads to more hydrophilic organoruthenium(8-oxyquinolinato) anticancer agents. Abstract : Ru(arene) compounds have many desirable features making them promising candidates for further development in anticancer drug research. While a lot of emphasis has been placed on the modification of the ancillary ligands, there are not many examples of arene ligands bearing functional groups. Herein, we report the preparation of [Ru(arene)(8-oxyquinolinato)Cl] complexes with the arene being a protected form of the amino acidl -phenylalanine and 8-oxyquinolinato ligand substituted with halogens. With this approach we aimed to alter the pharmacological properties of the complexes and address issues with the aqueous solubility of the analogous p -cymene complexes. The complexes were shown to be stable in DMSO and water and reacted readily withl -histidine and 9-ethylguanine as protein and DNA models, respectively. Assaying the antiproliferative activity in cancer cells gave IC50 values in the low μM range. While the lipophilicity of the p -cymene analogues correlated well with their in vitro cytotoxicity, the potency of the complexes with thel -phenylalanine-derived arene was independent of lipophilicity.